2016
DOI: 10.17083/ijsg.v3i1.106
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Cubes for Cognitive Gaming: Preliminary Usability and Game Experience Testing

Abstract: Early detection is important in dementia care; however, cognitive impairment is still under-recognised and under-diagnosed. Cognitive screening and training are two important preventative treatments, which can lead to early detection of cognitive decline. In this work, the “Cognitive Augmented Reality Cubes” (CogARC) system is presented, i.e. a serious game for cognitive training and screening, utilising an interaction technique based on Augmented Reality and the manipulation of tangible, physical objects (cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…The results revealed that these students succeeded in defining new science vocabulary terms with AR technology support. Boletsis et al [78] tested usability of AR-based cubes gaming system for adults. This game was developed for cognitive field.…”
Section: Using Augmented Reality In Other Target Groupsmentioning
confidence: 99%
“…The results revealed that these students succeeded in defining new science vocabulary terms with AR technology support. Boletsis et al [78] tested usability of AR-based cubes gaming system for adults. This game was developed for cognitive field.…”
Section: Using Augmented Reality In Other Target Groupsmentioning
confidence: 99%
“…A thorough literature review and taxonomy analysis 19,20 resulted in shaping of the characteristics and the theoretical description of the gaming system, 1,21 followed by an iterative development process and the examination of several interaction, game design, and game content aspects. 22,23 This article describes the design and development process of Smartkuber and, consequently, examines and studies the utility of the Smartkuber game as an entertaining and motivating tool for cognitive health screening of elderly players. Specifically, the study aims to (1) quantitatively evaluate the elderly players' game experience with Smartkuber and (2) investigate the use of Smartkuber for its construct, criteria (concurrent and predictive), and content validity, assessing its relationship with the MoCA test.…”
Section: Boletsis and Mccallummentioning
confidence: 99%
“…The cube-as a tangible physical object-is an accredited assistive tool for cognitive training, cognitive assessment, and motor rehabilitation, which addresses the players' cognitive and motor skills, while being a game element, which appeals to a wide target audience, from children to elderly players. 22,23,[28][29][30] AR is a technology, which is strongly connected with the users' perception as well as their cognitive and physical functionality. 21,22 In previous related studies, AR has been found to manifest technical and perceptual issues when cubes are digitally augmented with game content.…”
Section: Interaction Componentsmentioning
confidence: 99%
See 2 more Smart Citations